ANALISIS MODEL HAROLD HOTELLING DALAM PENENTUAN LOKASI BIMBINGAN BELAJAR - Ode Sofyan Hardi (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2015)
ABSTRACTThe purpose of this study 1) analyze the application of Harold Hotelling models in determining the location of tutoring (bimbingan belajar), 2) determine whether the theory is still relevant for today and for the type of service industry. Descriptive research is one of the types of research methods that seek to describe and interpret the object in accordance with what it is. By the time the research done on the Moon in March 2014 until December 2014, the unit of analysis in this study is tutoring available the Rawamangun ward, as well as some students from each of the learning guidance. Samples were taken using random samples with system lottery with the intention that each class has an equal chance of being sampled in the study. Samples taken as many as 4 tutoring. As well as students from each sample Bimbel 300 students. Analysis of the data in this study using descriptive statistical analysis.The results of the study explained that for the indicator in accordance with the theory of Harold Hotteling for determining the location of tutoring is spread evenly in the consumer market. In this indicator, the transportation cost rate per unit fixed cost of production of the same product and the difference in profit or loss of the company is only based on the position and location of the source material as well as all costs incurred depending on the situation and location of manufacturers serving the needs of the market. There is no differentiation ability of sellers to conduct market price levels except the only factor in the cost of transportation and every company has complete freedom to operate in the market without incurring the costs and demand is inelastic product is perfect, while the less fit is the indicator of the selling price per unit and the distance is fixed and the qualification level of the buyers and sellers comparable.Keywords: Learning; Guidance; Hotelling; Location